2023
DOI: 10.3390/app13095496
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Development, Dentofacial Disharmony, and Its Surgical Correction on Speech: A Narrative Review for Dental Professionals

Abstract: Speech is a communication method found only in humans that relies on precisely articulated sounds to encode and express thoughts. Anatomical differences in the maxilla, mandible, tooth position, and vocal tract affect tongue placement and broadly influence the patterns of airflow and resonance during speech production. Alterations in these structures can create perceptual distortions in speech known as speech sound disorders (SSDs). As craniofacial development occurs, the vocal tract, jaws, and teeth change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
(118 reference statements)
0
0
0
Order By: Relevance
“…With controls having the largest spectral amplitude followed by Class II non-AOB, and then all AOB, this could mean that Class II non-AOB patients are best able to posture so as to produce an alveolar constriction resulting in turbulence most similar to that produced by Class I controls. Most Class II patients present with deficient mandibles in which their tongues are also naturally positioned more posteriorly (see Bode et al, 2023 ), which contributes to a more similar constriction location compared to the controls. The AOB cohort has a more difficult time positioning the tongue tip and teeth to produce turbulence noise similar to that of the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With controls having the largest spectral amplitude followed by Class II non-AOB, and then all AOB, this could mean that Class II non-AOB patients are best able to posture so as to produce an alveolar constriction resulting in turbulence most similar to that produced by Class I controls. Most Class II patients present with deficient mandibles in which their tongues are also naturally positioned more posteriorly (see Bode et al, 2023 ), which contributes to a more similar constriction location compared to the controls. The AOB cohort has a more difficult time positioning the tongue tip and teeth to produce turbulence noise similar to that of the controls.…”
Section: Discussionmentioning
confidence: 99%
“… Grudziąż-Sękowska et al (2018) and Assaf et al (2021) found an association between malocclusion and speech distortion in children. See Bode et al (2023) for a more extensive review of the literature.…”
mentioning
confidence: 99%